2022
DOI: 10.1111/joca.12450
|View full text |Cite
|
Sign up to set email alerts
|

Stronger together: Developing research partnerships with social impact organizations

Abstract: A growing number of Transformative Consumer Research (TCR) academic community members are establishing research partnerships with Social Impact Organizations (SIOs) such as nonprofits, public policy entities, and other societally focused organizations and initiatives. These relational engagement partnerships with SIOs are vital for TCR researchers because SIOs have deep connections to people and communities where transformative change takes place. We leverage insights from TCR researchers and SIOs engaged in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Prior research in marketing and related fields has provided guidance on how to conduct community-based research (e.g., Ozanne and Anderson 2010) and how to develop research partnerships with social impact organizations like nonprofits, local government entities, and socially focused organizations serving the community (Bublitz et al 2022). It has introduced a typology of relational engagements that encourages researchers to partner with stakeholders such as policy makers, nonprofit organizations, business leaders, and consumer groups and defined different pathways for researchers to do so.…”
Section: Extensive Localized Social Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research in marketing and related fields has provided guidance on how to conduct community-based research (e.g., Ozanne and Anderson 2010) and how to develop research partnerships with social impact organizations like nonprofits, local government entities, and socially focused organizations serving the community (Bublitz et al 2022). It has introduced a typology of relational engagements that encourages researchers to partner with stakeholders such as policy makers, nonprofit organizations, business leaders, and consumer groups and defined different pathways for researchers to do so.…”
Section: Extensive Localized Social Problemsmentioning
confidence: 99%
“…Extensive localized social problems can create opportunities for research, practice, policy, and interventions to effect change, promote local health (Minkler 2005), and drive positive societal impact. Prior research has provided guidance on how researchers can establish partnerships with key stakeholders working to solve the challenges of interest (Bublitz et al 2022; Ozanne, Davis, and Ekpo 2022) and how to conduct research that addresses extensive localized social problems with a community-based approach that acknowledges the importance of community stakeholders in understanding the challenges and developing solutions (Ozanne and Anderson 2010). Extensive localized social problems also provide opportunities for innovative business models and approaches to be created in collaboration with key stakeholders through the development of research-based social enterprises, or hybrid organizations with a dual mission that includes market or economic objectives alongside social objectives (Saebi, Foss, and Linder 2019).…”
mentioning
confidence: 99%
“…This is argued to generate results that are better aligned with the needs of practitioners (Zeithaml et al, 2020). Engagement partnerships with social impact organizations can also help to bridge the researcher-practitioner gap (Bublitz et al, 2022).…”
Section: Managerial Relevance Of Academic Research In Marketingmentioning
confidence: 99%
“…We seek to do more with regard to measuring the impact of the research published in JPP&M and documenting demonstrated influence on public policy. This will require closer relationships with the federal, state, and local entities involved in policy creation to understand the role academic research plays in the process so that we can improve the dissemination of research to policy constituents and better measure the impact of research published in JPP&M. We also see a research opportunity in partnering with those directly involved in the policy making process, as collaboration may offer additional perspectives and ensure that results are communicated to constituents who can use them in creating, implementing, and evaluating policy solutions (see Bublitz et al 2022). To the extent that we can strategically strengthen relationships with policy makers, we will certainly increase the probability that the research published in JPP&M will play a role in shaping public policy and efforts aimed at promoting consumer, societal, and environmental well-being.…”
Section: Community As Our Core Competencymentioning
confidence: 99%